The effect of cinical pathways for bariatric surgery on perioperative quality of care - Ronellenfitsch, Ulrich; Schwarzbach, Matthias; Kring, Marie Anne-Christin; Kienle, Peter; Post, Stefan; Hasenberg, Till (Obesity surgery, 2012)
BackgroundBariatric surgery demands a multidisciplinary approach and enhanced recovery schemes. Such schemes are complex and cumbersome to introduce into practice. This study evaluates if a clinical pathway (CP) facilitates implementation of an enhanced recovery scheme in bariatric surgery with the goal of improving perioperative quality of care.MethodsWe compared 65 consecutive patients who underwent bariatric surgery in 2009 and were treated with a CP (CP group) with 64 consecutive patients treated without CP in 2007/2008 (pre-CP group). Process quality indicators were catheter management, postoperative mobilization, spirometer training, vitamin B supplementation, diet resumption, intake of supplement drinks, and length of stay. Outcome quality was measured through morbidity, mortality, re-operations, and re-admissions.ResultsIn the CP group, foley catheters were removed earlier (p < 0.0001), patients were mobilized more often on the surgery day (CP group 92.3% vs. pre-CP group 78.1%, p = 0.03), used spirometers more often (56.9% vs. 28.1%, p = 0.002), were more often supplemented with vitamin B (100% vs. 31.3%, p < 0.0001), and received oral supplement nutrition more often (100% vs. 59.4%, p < 0.0001). Median length of stay was shorter in the CP group (6 vs. 7 days, p = 0.007). There was no significant difference in mortality, morbidity, re-operations, and re-admissions.ConclusionsFollowing implementation of an enhanced recovery CP for bariatric surgery, several indicators of process quality improved while outcome quality remained unchanged. A CP seems useful for optimizing treatment of bariatric surgery patients according to enhanced recovery principles. However, future studies are required to better determine which elements of care can be improved most.